Two decades of radiological accidents direct causes, roots causes and consequences - Rozental Jose de Julio (Brazilian Archives of Biology and Technology, 2002)
Practically all Countries utilize radioisotopes in medicine, industry, agriculture and research. The extent to which ionizing radiation practices are employed varies considerably, depending largely upon social and economic conditions and the level of technical skills available in the country. An overview of the majority of practices and the associated hazards will be found in the Table IV to VII of this document. The practices in normal and abnormal operating conditions should follow the basic principles of radiation protection and the Safety of Radiation Sources, considering the IAEA Radiation Protection and the Safety of Radiation Sources, Safety Series 120 and the IAEA Recommendation of the Basic Safety Standards for Radiation Protection, Safety Series Nº 115. The Standards themselves underline the necessity to be able to predict the radiological consequences of emergency conditions and the investigations that should need to be done. This paper describes the major accidents that had happened in the last two decades, provides a methodology for analyses and gives a collection of lessons learned. This will help the Regulatory Authority to review the reasons of vulnerabilities, and to start a Radiation safety and Security Programme to introduce measurescapable to avoid the recurrence of similar events. Although a number of accidents with fatalities have caught the attention of the public in recent year, a safety record has accompanied the widespread use of radiation sources. However, the fact that accidents are uncommon should not give grounds for complacency. No radiological accident is acceptable. From a radiation safety and security of the sources standpoint, accident investigation is necessary to determine what happened, why, when, where and how it occurred and who was (were) involved and responsible. The investigation conclusion is an important process toward alertness and feedback to avoid careless attitudes by improving the comprehension of Safety Performance and Safety Culture. Accident investigation is the first step toward avoiding future injures and financial losses, by prevention of recur recurrence. On the other hand, accident investigation is also essential for the establishment of the responsibilities and liability for the consequences. This document discuss the main accidents that have happened in the last two decades, in terms of causes, consequences, similarities and lessons learned when sealed sources have been damaged, lost, stolen and abandoned. In considerable majority death and serious injuries were resulted from failures in the safety system for radiation sources and for the security of radioactive materials.